Upaya Peningkatan Kinerja Karyawan Pt Kokapura Bagian Check-In Counter Dan Boarding Gate Di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Efrika July Priyanto; Sri Sutarwati (Universitas Sains dan Teknologi Komputer, 2023)
Performance is a very important part of a company, without good performance from all employees, the company's goals are difficult to achieve. This study aims to determine the efforts made by PT. Kokapura in improving the performance of employees of the Check-In Counter and Boarding Gate at General Ahmad Yani International Airport Semarang. This research uses qualitative methods. This research data is obtained from primary and secondary data, The tools used are data collectors with the results of observation, interviews and documentation at the Check-In Counter and Boarding Gate units, observations, interviews and documentation as supporting documents to answer the formulation of research questions, then using data validity tests and finally researchers carry out data analysis techniques consisting of data reduction, Data Presentation and Conclusion Verification. The results of this study show that the first effort made by PT PT. Kokapura Performance is a very important part of a company, without good performance from all employees, the company's goals are difficult to achieve. This study aims to determine the efforts made by PT. Kokapura in improving the performance of employees of the Check-In Counter and Boarding Gate at General Ahmad Yani International Airport Semarang.